PECULIARITIES OF DEVELOPMENT AND EVOLUTION OF SCLERODERMIC DISEASE IN CHILDREN AND ADOLESCENTS - Lebets, I.S.; Bogmat, L.F.; Kashkalda, D.A.; Kashina, V.L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
On the basis of clinico-biochemical study of 52 patients with systemic and  limited  sclerodermia it was established some similarity between clinical symptoms, syndromes and tendencies in the changesof metabolic findings in connective tissue structures and the content of microelements in both nosological forms. The data obtained indicate the presence of common pathogenetic mechanisms of their development which makes it posible to consider systemic and limited sclerodermias as manifestation of one disease at various  stages of pathology process development.